Tuturan Ilokusi dalam Berita Meet Nite Live Bertema Politik di Metro TV - Kahfi, Fahman; Mushoffa, Zuyyinatul; Zahro, Nanda Fatimatuz; Wardani, Paramita Kusuma; Jauhari, Falah; Shofa, Anindha Naila; Yudi Utomo, Asep Purwo (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Political communication through television plays an important role in shaping public opinion. One of the political programs that attracts attention is Meet Nite Live on Metro TV, which presents discussions in a relaxed but sharp style. This study aims to identify the form of illocutionary speech acts in the program and analyze its function in conveying political messages. The method used in this study is descriptive qualitative with a descriptive methodological approach to explain the speech acts contained in the Meet Nite Live Metro TV broadcast. The data sources used in this study were all utterances contained in the Meet Nite Live Metro TV broadcast in a certain edition, while the data were in the form of excerpts of pragmatic discourse contained in the video broadcast which were suspected of being illocutionary speech acts. The data collection technique used was the listening and recording technique. The data obtained were analyzed using the matching and distribution methods. Furthermore, data presentation was carried out formally and informally. Based on the results of the analysis of this study, utterances were found to be illocutionary speech acts. There were four categories that appeared in the video, namely assertive, directive, commissive, and expressive. The most dominant category in this study is assertive speech acts with 6 utterances, followed by expressive with 4 utterances, commissive with 3 utterances, and directive with 2 utterances.